Pendapatan Asli Daerah Dan Dana Alokasi Khusus Terhadap Belanja Daerah Pada Kabupaten/Kota Provinsi Sumatera Barat - Putri, Cantika Rahmanda; Putra, Gerry Hamdani (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to test whether there is an influence of local original income and special allocation funds on regional spending at the Central Statistics Agency (BPS) of West Sumatra. The population in this study were 19 West Sumatra Regencies/Cities at the West Sumatra Central Statistics Agency (BPS). The samples used were 57 samples from the West Sumatra Central Statistics Agency (BPS). The sampling technique used documentation techniques. The research method used is quantitative with data sources in the form of secondary data. The data analysis method uses multiple linear regression analysis with Eviews 9. The results of this research provide empirical evidence that partially the variables of local original income and special allocation funds have a positive effect on regional spending. Simultaneously, the variables of local original income and special allocation funds have a positive effect on regional spending.